2008
DOI: 10.4067/s0718-16202008000300008
|View full text |Cite
|
Sign up to set email alerts
|

Heredabilidad de la sobrevivencia en 169 familias de maíz-roseta de granos blancos: Un enfoque Bayesiano

Abstract: El maíz-roseta (Zea mays ( ( L.) es un tipo de maíz que tiene la capacidad de expandirse y eventualmente reventar a altas temperaturas, generando un alimento sabroso y suave, el cual es apreciado en diferentes países consumidores del producto. En Brasil, existe una creciente demanda anual de maíz-roseta, donde se estima un consumo aproximado de 70.000 t•año -1 , de las cuales 71% son importadas principalmente de Argentina y Estados Unidos (Scapim et al., 2006). El número reducido de cultivares es un factor lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that the trait heritability of GY varies from low to moderate [ 66 , 67 ], indicating a lower additive genetic control and high environmental influence. However, other research has claimed that the heritability of GY is high and significant [ 68 , 69 ] and suggested, therefore, that these values depend on the population under study. In the UENF-14 population intrapopulation recurrent selection program, it was observed that heritability remained stable in cycles 4, 5 and 6 (45.97%, 51.94%, and 45.04%, respectively) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the trait heritability of GY varies from low to moderate [ 66 , 67 ], indicating a lower additive genetic control and high environmental influence. However, other research has claimed that the heritability of GY is high and significant [ 68 , 69 ] and suggested, therefore, that these values depend on the population under study. In the UENF-14 population intrapopulation recurrent selection program, it was observed that heritability remained stable in cycles 4, 5 and 6 (45.97%, 51.94%, and 45.04%, respectively) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%